Efficiency and productivity analysis of microfinance institutions in Asean -4 countries - Siti Nurzahira Che Tahrim
There are very limited studies in the efficiency of microfinance institution (MFIs) in the Association of Southeast Asian Nations (ASEAN) countries. From the review of the literatures, research done to compare the efficiency and productivity of MFIs in ASEAN countries is limited. Hence, the study of efficiency and productivity in this region is significant and will contribute to the existing literature. The purpose of this study is to examine and compare the efficiency levels and productivity changes of MFIs in four countries in ASEAN; which are Indonesia, the Philippines, Vietnam and Cambodia, during the period of 2008 to 2011 by employing the non-parametric ata Envelopment pproach (DEA) and Dynamic Malmquist Productivity Index (MPI). The findings reveal that the MFIs in ASEAN-4 countries have exhibited an overall efficiency of 75.5% 'during 2008 to 2011 suggesting an input waste of 24.5%. The overall efficiency has recorded the highest in 2008 (76.5%) and the lowest in 2009 (74.6%). The trend has increased since 2009 to 75.7% in 2011. The main contributor to inefficiency on average across the years is the pure technical inefficiency, which implies that skills in managing the inputs need improvement to enhance efficiency levels. In terms of country, Vietnam is the most technically efficient (91.4%) country in ASEAN-4, followed by Cambodia (80.9%), Indonesia (73.8%) and the Philippines (66.4%). Using Dynamic MPI, the results showed that the MFIs in ASEAN-4 countries have exhibited the average total factor productivity change regress in 2009 by 1.9%, progress in 2010 and 2011 at 0.4% and 0.3% respectively. Reduction in change of technological and pure technical efficiency caused the regress in 2009. The progress in 2010 is due to improvement in technology and scale efficiency, while pure technical efficiency growth contributed the most to productivity progress in 2011. This implies that all three components of productivity (technological, pure technical and scale) affected the regress and progress of productivity in ASEAN-4 countries during the study period. When decomposing the efficiency change into pure technical and scale efficiency change, results from both DEA and MPI support that the dominant source of efficiency was scale related rather than pure technically related. This implies that MFls have been operating at an appropriate scale of operations, but relatively inefficient in managing their assets and operating costs. The results of the study suggest that in order to enhance ASEAN microfinance efficiency and productivity, the regulators need to provide training to microfinance institutions to improve their managerial and technical skills.